Antarctic root endophytes improve physiological performance and yield in crops under salt stress by enhanced energy production and Na+ sequestration - Marco A. Molina-Montenegro (Nature Portfolio, 2020)
Abstract Climatic change is pointed as one of the major challenges for global food security. Based on current models of climate change, reduction in precipitations and in turn, increase in the soil salinity will be a sharp constraint for crops productivity worldwide. In this context, root fungi appear as a new strategy to improve plant ecophysiological performance and crop yield under abiotic stress. In this study, we evaluated the impact of the two fungal endophytes Penicillium brevicompactum and P. chrysogenum isolated from Antarctic plants on nutrients and Na+ contents, net photosynthesis, water use efficiency, yield and survival in tomato and lettuce, facing salinity stress conditions. Inoculation of plant roots with fungal endophytes resulted in greater fresh and dry biomass production, and an enhanced survival rate under salt conditions. Inoculation of plants with the fungal endophytes was related with a higher up/down-regulation of ion homeostasis by enhanced expression of the NHX1 gene. The two endophytes diminished the effects of salt stress in tomato and lettuce, provoked a higher efficiency in photosynthetic energy production and an improved sequestration of Na+ in vacuoles is suggested by the upregulating of the expression of vacuolar NHX1 Na+/H+ antiporters. Promoting plant-beneficial interactions with root symbionts appears to be an environmentally friendly strategy to mitigate the impact of climate change variables on crop production.